Efficacy and safety of the contraceptive vaginal ring (NuvaRing) compared with a combined oral contraceptive in Chinese women: a 1-year randomised trial. (3rd July 2016) - Fan, Guang Sheng; Ren, Mulan; Di, Wen; Su, Ping; Chang, Qin; Wu, Shuying; Qin, Yun; Korver, Tjeerd; Marintcheva-Petrova, Maya; Yacik, Carol; McCrary Sisk, Christine; Wang, Guoqin
Abstract: Objectives: The aim of the study was to assess the efficacy and tolerability of the monthly vaginal ring (NuvaRing; 15 μg ethinylestradiol [EE] and 120 μg etonogestrel per day) compared with a monophasic (21/7) combined oral contraceptive (COC) containing 30 μg EE and 3 mg drospirenone in healthy Chinese women aged 18–40 years. Methods: This was a phase III, open-label, randomised multicentre trial conducted in China. Participants received NuvaRing or COC for 13 cycles (3 weeks of ring/pill treatment followed by a 1-week ring-free/pill-free period). Contraceptive efficacy was assessed by in-treatment pregnancies and expressed by the Pearl Index (PI; number of pregnancies/100 woman-years of use). Cycle control was assessed by unscheduled (breakthrough) and absence of scheduled (withdrawal) bleeding events. Safety and tolerability were assessed throughout the study. Results: Participants were randomised either to the NuvaRing ( n = 732) or to the COC ( n = 214); 588 (82.4%) and 182 (78.4%) participants, respectively, completed the study. There were 10 in-treatment pregnancies in the NuvaRing group (PI 1.92; 95% confidence interval [CI] 0.92, 3.53) and five in the COC group (PI 3.12; 95% CI 1.01, 7.29). Breakthrough bleeding/spotting ranged from 18.6% (Cycle 1) to 4.2% (Cycle 11) for NuvaRing and from 21.6% (Cycle 1) to 7.9% (Cycle 11) for COC. Absence of withdrawal bleeding ranged from 8.6% (Cycle 1) to 3.0% (Cycle 11) for NuvaRing and from 14.6% (Cycle 1) to 6.4% (Cycle 5) for COC. For NuvaRing and COC, respectively, 26.6% and 25.0% of participants had treatment-related adverse events, and 7.0% and 9.1% discontinued the study as a result. Conclusions: Once-monthly NuvaRing is efficacious and safe for use in Chinese women.